2018
DOI: 10.1002/gps.5001
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in older people admitted to hospital: An analysis of length of stay and associated costs

Abstract: Objectives Patients with dementia in the acute setting are generally considered to impose higher costs on the health system compared to those without the disease largely due to longer length of stay (LOS). Many studies exploring the economic impact of the disease extrapolate estimates based on the costs of patients diagnosed using routinely collected hospital discharge data only. However, much dementia is undiagnosed, and therefore in limiting the analysis to this cohort, we believe that LOS and the associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In a study comparing patients discharged from psychiatric hospitals in Turkey with similar patients in Ireland, the presence of delirium or dementia was not associated with LOS, but the proportion of such patients in the sample was low: 13.6 per cent in Turkey and 25.5 per cent in Ireland; the only factor significantly associated with LOS was living alone (Carpar et al, 2018). In the last mixed-results study, a trend towards longer stay was seen for dementia patients, which was only significant in the subgroup who lived with a family member (11.61 vs. 7.55 days, p = 0.002) (Ahern et al, 2019). Authors also found that people with dementia admitted for a surgical procedure had a shorter stay than people without dementia (2.4 vs. 5.87 days, p = 0.001).…”
Section: Association Between Cognitive Impairment and Los Or Ddmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study comparing patients discharged from psychiatric hospitals in Turkey with similar patients in Ireland, the presence of delirium or dementia was not associated with LOS, but the proportion of such patients in the sample was low: 13.6 per cent in Turkey and 25.5 per cent in Ireland; the only factor significantly associated with LOS was living alone (Carpar et al, 2018). In the last mixed-results study, a trend towards longer stay was seen for dementia patients, which was only significant in the subgroup who lived with a family member (11.61 vs. 7.55 days, p = 0.002) (Ahern et al, 2019). Authors also found that people with dementia admitted for a surgical procedure had a shorter stay than people without dementia (2.4 vs. 5.87 days, p = 0.001).…”
Section: Association Between Cognitive Impairment and Los Or Ddmentioning
confidence: 86%
“…It is of note that LOS or DD are also influenced by other factors inherent in the patient, for example, the causes of hospitalization and co-morbidities (Fick, Steis, Waller, & Inouye, 2013). Such factors, including admission diagnoses, could therefore be confounding the association between CI and LOS or DD (Ahern et al, 2019) by leading to a specific health care trajectory. Conversely, the self-management of some health issues may require greater cognitive function and could play a role in delayed discharge in less-severely impaired patients who desire to return home but may need additional services not readily available (Costa & Hirdes, 2010;Costa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The DASS-21 is a self-report questionnaire assessing levels of caregiver stress, anxiety and depression over the previous seven [7] day period. The results provide an indication of the individual's perception of their experience of depression, anxiety and stress.…”
Section: Methodsmentioning
confidence: 99%
“…A further 9.9 million new cases of dementia worldwide are predicted each year [5] as populations around the globe continue to live longer [6]. These figures could be very much under estimated as it is widely accepted that between 50 and 80% of people affected have no formal dementia diagnosis [7]. This growing epidemic effects not only the individuals living with dementia, but also their families caring for them, the communities they live in and the health care systems they rely upon.…”
Section: Introductionmentioning
confidence: 99%
“…• Reducing specialling saves money • Opportunities • Real-time debriefing/huddles (Ahern et al, 2018) Prospective cohort study.…”
Section: Themes -Antecedents (What Happens Before?)mentioning
confidence: 99%